SCOPE OF VARYING PROOF IN FAMILY LAW - Sivapatham, M. (A thesis submitted for the Degree of Master of Laws, 1993)
In the Introductory Chapter the areas of varying proof in Family Law are identified with reference to the concepts of legitimacy, marriage, death and adultery. It has to be pointed out that the sole object of proof in any dispute is to ascertain the truth. Variation in proof may crop up in two situations. This may occur, either in the burden of proof or in the standard of proof or in both. It may be pointed out that variation in proof in the above areas in civil proceedings result mostly due to the operation of presumptions. The effectiveness of presumptions in proof on the above areas of family Law will be 'iscussed in Chapter 1 and causes for the degree of variation will be discussed in the Chapters that follow. Chapter 2 deals with the concept of presumption of legitimacy. The factors, which have a positive, negative and neutral impacts upon the presumption of legitimacy will be discussed in this Chapter in detail. More over possible or desirable suggestions are made with a view to promoting (he state policy and social justice by protecting the interests of children when their paternity becomes questionable. In the third Chapter, legal assumptions with regard to the presumption of marriage will be examined. Due to the lack of a common matrimonial code for all communities, variations in proof of the validity of marriages is in existence in the areas of customary marriages, marriages by habit and repute and putative marriages. The purpose of both substantive and procedural laws is to maintain social justice. It is therefore, obvious that any change in attitude in substantive (X) law may lead to deviation from justice till such time corresponding changes are introduced in the procedural law as well. This type of variation generally falls within the standard of proof in civil proceedings. This is discussed in Chapter 4, dealing with the concept of adultery in matrimonial actions. It is felt that proof of death and time of death is often a difficult task in the present growing dynamic society. Due to the operation of conflicting presumptions (ie.presumptions of continuance of life and presumption of death) establishing the presumption of death in a civil proceeding becomes a difficult task. Also when presumptions are made they become rather difficult to rebut. It will be seen that when a death is in question the presumption of same, compared with other presumptions, does not have any presumptive value as it merely regulates the burden of proof. The question of the time of death will be considered in the light of English Law as there is apparently a lacuna in our law. The solution for the above conflicting issues will be ascertained in the light of English and Sri Lankan cases in Chapter 5. Finally, I have pointed out in the concluding Chapter that in the absence of definite norms in substantive and procedural laws in determining factual situations a risk of jeopardising social justice by tribunal is discernible. It may thus be concluded that the aim of this paper is to identity the conflicting ends of the pendulum, one end with procedural and substantive laws and the other end with justice. From the above discussions, it could be asserted that the most possible and desirable standard of proof which could be applied in all civil proceedings within Family Law, is the third standard, of the application of the rule of cogent evidence which will go along the via media policy to ensure uniformity.